1993
DOI: 10.4141/cjas93-005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing steers fed either hay or silage supplemented with canola or fish meal

Abstract: One hundred and eighty-six crossbred steers (194.4 ± 1.5 kg) were used to determine the effect of protein supplementation of medium-quality grass hay or silage on performance during wintering and compensatory growth during the grazing period. All steers received the hay or the silage ad libitum during the 182-d wintering period. They were also fed fixed quantities of one of three supplements: C, a control with no supplemental protein; CM, a canola meal; and FM, a fish meal containing supplements. Daily amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The response to protein supplementation on forage DM intake might depend on forage conservation. Seoane et al (1993) observed that protein supplementation increased intake of forage when it was fed as hay while there was no effect when it was fed as silage. It has been suggested that silage intake is not improved by protein supplementation unless a parallel increase in digestibility is observed (Steen 1988).…”
Section: Growth Trialmentioning
confidence: 98%
See 2 more Smart Citations
“…The response to protein supplementation on forage DM intake might depend on forage conservation. Seoane et al (1993) observed that protein supplementation increased intake of forage when it was fed as hay while there was no effect when it was fed as silage. It has been suggested that silage intake is not improved by protein supplementation unless a parallel increase in digestibility is observed (Steen 1988).…”
Section: Growth Trialmentioning
confidence: 98%
“…Forages constitute a natural and plentiful resource in Quebec, thus their utilization for lamb production is being encouraged. Although most early-harvested forages meet the theoretical protein requirements of growing ruminants, protein supplementation usually enhances performance of growing beef cattle (Veira et al 1985;Seoane et al 1993), and this effect has not been necessarily related to higher DE intake (Seoane et al 1992). It remains to be clarified if the beneficial effect of protein supplementation depends on the ruminal degradability of the protein being fed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, results depend upon the nature of nitrogen in the concentrate as there are different mechanisms involved in the microbial and animal response to supplementation (Seoane et al, 1993). Nitrogen supplementation is generally based on soybean meal (SBM) which is costly.…”
Section: Introductionmentioning
confidence: 99%
“…In review of literature, also agree the result that DMI increase with supplying the higher (10%) amount of FM. Another scientist (Petit and Flipot., 1992;Seoane et al, 1993;and Veira et al, 1994) agree that FM supplementation increased DMI in cattle fed silage diets. …”
Section: Effect Of Fm On Dry Matter Intake Of Crossbred Heifersmentioning
confidence: 99%